"They Turned It Against Us." How the Rape Kit Failed Sexual Assault Survivors and Their Allies: A Brief History - Quinlan, Andrea (Canadian Woman Studies/les cahiers de la femme, 2019)
Graphic zine illustrating the history of the rape kit.